Effect of Adding Probiotic Yeast and Fermentation Time on Probiotic Tempeh Characteristics - Qibty, Mari'ah; Yulianto, Wisnu Adi; Pujimulyani, Dwiyati (Journal of Food and Agricultural Technology, 2023)
Tempeh is one of the foods made from soybean seeds or other ingredients that are processed through fermentation. Tempeh currently circulating in the community does not contain probiotic yeast, the addition of probiotic yeast is intended to provide probiotic properties to tempeh. From previous studies, yeast isolates from radishes and tomatoes have been identified as potential probiotic yeasts. This study aimed to determine the effect of adding the type of probiotic yeast isolate and fermentation time on the number of fungi, the number of yeasts, pH, antioxidant activity, and the level of preference by panelists for the resulting probiotic tempeh. This study used a completely randomized design with a factorial pattern. The first factor was the type of probiotic inoculum (Saccharomyces boulardii, yeast isolate LBK K, yeast isolate TMT 2), and the second factor was incubation time (0 hours, 24 hours, and 48 hours). The analysis included the number of fungus and yeast (plate count agar), antioxidant activity (radical scavenging activity (%), and preference level for probiotic tempeh. The data obtained were analyzed for variance (ANOVA) at a 95% confidence level. If there was a significant difference between each treatment was continued with Duncan's multiple range test (DMRT). The results showed that adding probiotic yeast type and a long incubation time affected the microbiological properties, antioxidant activity, and panelist preference. The most preferred tempeh was tempeh with the addition of LBK K isolate with an incubation time of 48 hours with a pH of 5.46, the total number of fungi was 6.62 log CFU/g, the total amount of yeast was 8,63 log CFU/g, the antioxidant activity was 18.58% RSA. Tempeh, with the addition of LBK K yeast isolate, has the potential as a probiotic food.